Cloning of endo-β-1,4 glucanase from aspergillus niger and its expression in saccharomyces cerevisiae - Viet Cuong, Pham; Dinh Thi, Quyen; Quyen, Vu Thi; Thi Kim Cuc, Nguyen (Vietnam Journal of Science and Technology, 2017)
Endoglucanase is one of the three forms of cellulase enzymes, widely used in different industries, and has been synthesized by animals, plants and microorganisms. β-glucanase is one of the feed enhancing enzymes, so adding of β-glucanase to the feed originated from plants, it can not only enhance their nutritional quality greatly, but also resolve the digestion problems of chickens/pigs due to high amount of β-glucan in these kinds of feed. In this work, β-glucanase gene from A. niger was ligated in expression vector pESC-His and expressed in S. cerevisiae KY117. EglB gene was cloned in pCR2.1 vector, then ligated in expression vector pESC-His using T4 ligase enzyme after cleaving both recombinant pCR2.1/ EglB and pESC-His by BamHI and XhoI. Using protoplast fusion method, recombinant pESC-His/EglB was transformed into competent S. cerevisiae KY117 strains. Transformants were verifyed by PCR using specific primers GAL10 for pESC-His plasmid. Recombinant S. cerevisiae KY117 was cultured in SC-His and induced by galactose. Total protein was subjected to SDS-PAGE and the obtained result showed that after 60 hours incubation, the protein with molecular weight about 17kDa was induced, corresponding with theoretical EglB. Biological activity of the expressed protein was tested based on CMC-ase activity of recombinant KY117. The strains without recombinant plasmid did not digest CMC in the medium, meanwhile recombinant S. cerevisiae KY117 made clearly unstained circular zone around the wells after staining CMC plates with Congo red